PERCEPTIONS OF TRANSFORMATIONAL LEADERSHIP, TRANSACTIONAL AND JOB SATISFACTION AS PREDICTOR OF EMPLOYEE ORGANIZATION COMMITMENT PT X MAKASSAR (PERSEPSI TERHADAP KEPEMIMPINAN TRANSFORMASIONAL, TRANSAKSIONAL DAN KEPUASAN KERJA SEBAGAI PREDIKTOR KOMITMEN ORGANISASI KARYAWAN PT X MAKASSAR) - Ria Febriani; Arie Gunawan HZ; Andi Budhy Rakhmat; Dedi Nasruddin (State Islamic University (UIN) Ar-Raniry, 2022)
The company will strive to be able to mobilize all the abilities, efforts and best performance of employees in order to achieve organizational goals. The success of employees in carrying out tasks cannot be separated from the role of leadership in directing employees so as to minimize errors in carrying out task completion. The role of the leader in providing direction and support in order to create a close relationship between leaders and subordinates in a work atmosphere. Every leader has a way or style in an effort to influence or direct employees to achieve the goals that have been agreed in the organization or company. The style or form of leadership that reflects the behavior pattern of the leader in influencing and directing subordinates will determine success in achieving organizational goals. Therefore, this study aims to see whether perceptions of transformational, transactional leadership and job satisfaction can be predictors of organizational commitment of PT X Makassar employees. This research uses a correlational quantitative approach. The subjects in this study were employees of PT X Makassar which were determined by generalization as many as 158 employees. The results showed that (1). Perception of transformational leadership can be a predictor of organizational commitment with a significance value of 0.000 (sig. < 0.005) and an R square of 14.3%. (2). The perception of transactional leadership cannot be a predictor of organizational commitment with a significance value of 0.441 (sig. < 0.005) and an R square of 0.3%. (3). Job satisfaction can be a predictor of organizational commitment with a significance value of 0.0003 (sig. < 0.005) and R square of 4.9%. (4). Perceptions of transformational leadership, transactional and job satisfaction together can be a predictor of organizational commitment with an R square value of 19.6%.Â Perusahaan akan berusaha keras untuk dapat mengerahkan segala kemampuan, usaha dan kinerja terbaiknya karyawan agar dapat mencapai tujuan organisasi. Keberhasilan karyawan dalam mengerjakan tugas tidak terlepas peran pimpinan dalam mengarahkan karyawan sehingga meminimalisir kesalahan dalam pelaksanaan penyelesaian tugas. Peran pemimpin dalam memberikan pengarahan dan dukungan agar tercipta hubungan akrab antara pimpinan dan bawahan dalam suasana kerja. Setiap pemimpin memiliki cara ataupun gaya dalam usaha mempengaruhi maupun mengarahkan para karyawan dalam mencapai tujuan yang telah disepakati dalam organisasi maupun perusahaan. Gaya atau bentuk kepemimpinan yang mencerminkan pola tingkah laku pemimpin dalam mempengaruhi serta mengarahkan bawahan sangat menentukan keberhasilan dalam mencapai tujuan organisasi. Oleh karena itu, penelitian ini bertujuan untuk melihat apakah persepsi terhadap kepemimpinan transformasional, transaksional dan kepuasan kerja dapat menjadi prediktor komitmen organisasi karyawan PT X Makassar. Penelitian ini menggunakan jenis pendekatan kuantitatif korelasional. Subjek pada penelitian ini adalah karyawan PT X Makassar yang ditentukan secara generalisasi yaitu sebanyak 158 karyawan. Hasil penelitian menunjukkan bahwa (1). Persepsi terhadap kepemimpinan transformasional dapat menjadi prediktor komitmen organisasi dengan nilai signifikansi 0.000 (sig. < 0.005) dan R square sebesar 14.3%. (2). Persepsi terhadap kepemimpinan transaksional tidak dapat menjadi prediktor komitmen organisasi dengan nilai signifikansi 0.441 (sig. < 0.005) dan R square sebesar 0.3%. (3). Kepuasan kerja dapat menjadi prediktor komitmen organisasi dengan nilai signifikansi 0.0003 (sig. < 0.005) dan R square sebesar 4.9%. (4). Persepsi terhadap kepemimpinan transformasional, transaksional dan kepuasan kerja secara bersama-sama dapat menjadi prediktor terhadap komitmen organisasi dengan nilai R square sebesar 19.6%.